Prof. Boris Sepesi: patient-personalized treatment is the best treatment - Jia, Zhuoqi; Wu, Shuang; Zhong, Jessie (Journal of Thoracic Disease; Vol 9, No 10 (October 31, 2017): Journal of Thoracic Disease, 2017)
© Journal of Thoracic Disease. All rights reserved. jtd.amegroups.com J Thorac Dis 2017 On May 31, 2017, the 25th Meeting of the European Society of Thoracic Surgeons (ESTS) successfully ended, after a 4-day scientific and compact agenda. The event took place in Innsbruck, a historical town located at the heart of the Alps, and the capital of the Tyrol, Austria. With a history of 25 years’ development, the ESTS conference has developed into the largest international event in the field of thoracic surgeons, with a reputation of excellent scientific and educational value.